The effectiveness of sugar tax in controlling sugar consumption - Haniyah, Rizqi; Johantri, Bagas; Sustiyo, Joko (Educoretax, 2025)
Excessive sugar consumption contributes to the increasing prevalence of obesity and chronic diseases such as type II diabetes mellitus and cardiovascular diseases. Indonesia ranked fifth in the number of diabetes cases in 2021, and this number is projected to rise to 28.6 million by 2045. One policy to control sugar consumption is the implementation of a sugar tax on sugar-sweetened beverages (SSBs). This study employs a systematic literature review (SLR) approach to analyze the impact of the sugar tax from economic, social, and political perspectives. Out of 2,719 articles being initially screened, 18 relevant articles were selected for analysis. The findings indicate that the effectiveness of the sugar tax depends on the tax rate, implementation strategies, and stakeholder support. Furthermore, the success of this policy requires cross-ministerial coordination, public education, and transparency in revenue allocation. Without a multidisciplinary approach, the sugar tax risks becoming a controversial policy that merely serves as a government revenue source.